(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, scientific researches were carried out on the preparation of plant seeds for processing, improvement of existing devices that meet the current requirements, creation of aspiration and separation processes and devices for the size and mass of seeds, creation of devices with low energy consumption.